ERP measures of semantic richness: the case of multiple senses - Taler, Vanessa; Kousaie, Shanna; Lopez Zunini, Rocio (Frontiers in Human Neuroscience, 2013)
Semantic richness refers to the amount of semantic information that a lexical item possesses. An important measure of semantic richness is the number of related senses that a word has (e.g., TABLE meaning a piece of furniture, a table of contents, to lay aside for future discussion, etc.) We measured electrophysiological response to lexical items with many and few related senses in monolingual English-speaking young adults. Participants performed lexical decision on each item. Overall, high-sense words elicited shorter response latencies and smaller N400 amplitudes than low-sense words. These results constitute further evidence of the importance of semantic richness in lexical processing, and provide evidence that processing of multiple related senses begins as early as 200 milliseconds after stimulus onset.